2016
DOI: 10.1084/jem.20151136
|View full text |Cite
|
Sign up to set email alerts
|

Loss ofEzh2synergizes withJAK2-V617F in initiating myeloproliferative neoplasms and promoting myelofibrosis

Abstract: Skoda et al. provide new insights into the collaboration between epigenetic regulator Ezh2 and a key hematopoietic tyrosine kinase in disease initiation and progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
82
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(92 citation statements)
references
References 49 publications
0
82
1
Order By: Relevance
“…43 To identify HMGA2 targets in the setting of MPNs, we performed RNA sequencing (RNA-seq) of LSKs from WT, DHmga2, JAK2 V617F , and ΔHmga2/JAK2 V617F mice, as well as JAK2 V617F / Ezh2 D/D mice based on recent reports showing that Ezh2 KO deteriorates MPNs with upregulating endogenous Hmga2 expression in HSPCs of mice with JAK2V617F. [27][28][29] Relative to WT, DHmga2/ JAK2 V617F mice showed the greatest change in the gene expression profile among genotypes ( Figure 5A). We found that 148 of 443 genes (33.4%) or 362 of 809 genes (44.7%) were upregulated in DHmga2/JAK2 V617F mice compared with JAK2 V617F mice or WT mice, respectively, overlapped with those of JAK2…”
Section: Hmga2 Overexpressionmentioning
confidence: 99%
See 1 more Smart Citation
“…43 To identify HMGA2 targets in the setting of MPNs, we performed RNA sequencing (RNA-seq) of LSKs from WT, DHmga2, JAK2 V617F , and ΔHmga2/JAK2 V617F mice, as well as JAK2 V617F / Ezh2 D/D mice based on recent reports showing that Ezh2 KO deteriorates MPNs with upregulating endogenous Hmga2 expression in HSPCs of mice with JAK2V617F. [27][28][29] Relative to WT, DHmga2/ JAK2 V617F mice showed the greatest change in the gene expression profile among genotypes ( Figure 5A). We found that 148 of 443 genes (33.4%) or 362 of 809 genes (44.7%) were upregulated in DHmga2/JAK2 V617F mice compared with JAK2 V617F mice or WT mice, respectively, overlapped with those of JAK2…”
Section: Hmga2 Overexpressionmentioning
confidence: 99%
“…Therefore, the loss of PRC2 members might be associated with the upregulation of HMGA2 in patients as in mice. [27][28][29] We then investigated the expression of HMGA2 in biopsied BM. HMGA2 is highly expressed primarily in hematopoietic cells, especially the nucleus of megakaryocytes ( Figure 6D), suggesting the possibility that HMGA2 correlates with proliferation of megakaryocytes in these patients as in JAK2 V617F mice overexpressing HMGA2.…”
Section: V617f /Ezh2mentioning
confidence: 99%
“…JAK2V617F/Ezh2 2/2 double mutant mice had significantly reduced survival due to rapid acceleration to lethal MF. [85][86][87] Furthermore, strong cooperation between Ezh2 loss and JAK2V617F on disease initiation by increasing the fitness of JAK2V617F stem cells was reported. At the cellular level, Ezh2 loss increased megakaryopoiesis at the expense of erythropoiesis.…”
mentioning
confidence: 99%
“…The overexpression of Hmga2, a gene that was previously found deregulated in human PMF, appears to play an important role in this phenotype. 86,87 ASXL1 and SRSF2 mutations are associated with a poor prognosis ASXL1 encodes for an epigenetic regulator, which binds to chromatin. Interestingly, it has been shown that ASXL1 recruits the PRC2 complex to specific loci through a direct interaction between ASXL1 and EZH2 88 ( Figure 4).…”
mentioning
confidence: 99%
“…In addition, the loss of Ezh2 enhanced the initiation and progression of RUNX1 mutant-induced MDS, but attenuated the predisposition to leukemic transformation [37], consistent with an oncogenic effect of Ezh2 in MLL-AF9-induced AML. We and other groups have also demonstrated that Ezh2 loss significantly promotes the development of JAK2 V617F mutant-induced myelofibrosis (MF), at least in part, due to the enhancement of aberrant megakaryocytopoiesis, which is thought to be critical for the formation of fibrosis [46][47][48]. These results clearly indicate that EZH2 plays a tumor suppressive role in myelodysplastic and myeloproliferative disorders that originate from HSCs.…”
Section: Kd Ezh2mentioning
confidence: 70%